PERISTILAHAN TRADISI SEKEME’AN PADA BULAN REBBE DAN PASAH MASYARAKAT MADURA DUSUN PARIT BUGIS - Matsudi Matsudi; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractIn tradition terms, sekemean Madurese people ditch the bugis ditch aimed to preserve knowledge of terms in culture. The problem in this study was the importance of the term in celebrating the tradition of sekemean in the month of rebbe and pasah as the belief of the Madurese people in welcoming fasting and the end of the fasting month. This study used descriptive methods through qualitative and quantitative studies. The approach used is an ethnolinguistic approach. Based on data analysis, researchers draw conclusions as follows; (a) language units (b) lexical and cultural meanings (c) terminological retention of the term sekemean tradition in the month of rebbe and pasah of the old, adult, and teenagers of the ditch village of Bugis, the village of Limestone. The researcher found 54 terms, where for the first problem there was a certain form of language unit term used by the Madurese trenches bugis in the tradition of sekemean. First, the basic word was 41 lexemes. Second, there were 4 basic words in the form of materials and 17 lexemes in the form of tools. There eare 1 invented words of material and in the form of tools there are 2 lexemes. The form of the phrase in the form of material was 10 and in the form of tools there are 7 lexemes. Third, lexical nominations in the form of phrases that are dominated by exocentric ware 13 lexemes. Keywords: Month Rebbe and Pasah Sekemean The Terminology Tradition